Adaptation of the Problem Management Plus programme for Syrian, Eritrean and Afghan refugee youth. (30th September 2020) - Alozkan Sever, C; Cuijpers, P; Bryant, R; Dawson, K; Mittendorfer-Rutz, E; Holmes, E; Sijbrandi, M
Abstract: Background: Common mental health problems are prevalent among refugee minors and impair their daily functioning. Due to various barriers such as lack of culturally appropriate treatments, waiting lists, and stigma they have limited access to care. Problem Management Plus (PM+) was developed by the World Health Organization to address these barriers. PM+ is transdiagnostic, delivered by non-professional helpers, and consists of 5 sessions of problem-solving skills, behavioural activation and stress management. PM+ is effective in reducing adults' distress and improve functioning. We aimed to adapt PM+ for refugee minors and add an emotional processing module to target symptoms of posttraumatic stress disorder. Methods: We culturally and contextually adapted PM+ for use in Syrian, Eritrean and Afghan refugee minors (age 16-18 years). Data were collected through: 1) free list interviews with Syrian, Eritrean and Afghan refugee minors (n = 30), 2) key informant interviews with knowledgeable refugees (n = 6), professionals (n = 6), policy makers (n = 6) and 3) focus group discussions (n = 24). Data were analysed in ATLAS.ti through inductive and deductive framework analysis. Results: The interviews with youth revealed daily life problems around the following themes: language, family and peers, and substance use. The overall results suggested the need for culture- and age-specific adaptations of 1) the PM+ manual content (language, metaphors, illustrations) and 2) intervention delivery (modality, content and presentation of the trauma processing module, and duration). Conclusions: This study led to specific adaptations of PM+ for refugee adolescents to be used in two randomized controlled trials in the Netherlands and Sweden. Key message: Refugee minors face numerous barriers reaching mental health care. Scalable, culturally adapted psychological interventions should be developed and evaluated to address common mental disorders in refugee youth.